The Role of LncRNAs in the Regulation of Radiotherapy Sensitivity in Cervical Cancer - Zhang, Hanqun; Fang, Chunju; Feng, Zhiyu; Xia, Tingting; Lu, Liang; Luo, Min; Chen, Yanping; Liu, Yuncong; Li, Yong (Frontiers in Oncology, 2022)
Cervical cancer (CC) is one of the three majors gynecological malignancies, which seriously threatens women's health and life. Radiotherapy (RT) is one of the most common treatments for Cervical cancer, which can reduce local recurrence and prolong survival in patients with Cervical cancer. However, the resistance of cancer cells to Radiotherapy are the main cause of treatment failure in patients with Cervical cancer. Long non-coding RNAs (LncRNAs) are a group of non-protein-coding RNAs with a length of more than 200 nucleotides, which play an important role in regulating the biological behavior of Cervical cancer. Recent studies have shown that LncRNAs play a key role in regulating the sensitivity of radiotherapy for Cervical cancer. In this review, we summarize the structure and function of LncRNAs and the molecular mechanism of radiosensitivity in cervical cancer, list the LncRNAs associated with radiosensitivity in cervical cancer, analyze their potential mechanisms, and discuss the potential clinical application of these LncRNAs in regulating radiosensitivity in Cervical cancer.